Different approaches for Agrobacterium-mediated genetic transformation of Brachypodium distachyon, a new model plant for temperate grasses - Zombori, Zoltán; Szécsényi, Mária; Györgyey, János (Acta Biologica Szegediensis, 2011)
Cereal crops belonging to temperate grasses are fundamental sources of human nutrition therefore their agronomical improvement is centrally important. For this purpose the establishment of an experimental model system for these monocot plants is essential in plant biology research. Considering its advantageous morphological and physiological virtues taken together with the results of the advanced genomics research the Brachypodium distachyon became the new model plant for the Poaceae. The aim of our work is to adapt and possibly improve the Agrobacterium-mediated transformation method using embryogenic callus from in vitro cultures and furthermore develop an in planta methodology via Agrobacterium tumefaciens for Brachypodium in order to simplify the transformation procedure.